2006
DOI: 10.1186/1745-9974-2-1
|View full text |Cite
|
Sign up to set email alerts
|

The description of cough sounds by healthcare professionals

Abstract: Background: Little is known of the language healthcare professionals use to describe cough sounds. We aimed to examine how they describe cough sounds and to assess whether these descriptions suggested they appreciate the basic sound qualities (as assessed by acoustic analysis) and the underlying diagnosis of the patient coughing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…A previous investigation by Smith et al has shown the ability of health care professionals to distinguish between these types of cough with a high accuracy by listening solely to the sound of cough. 17 If an epoch contained at least one productive cough event, the epoch was classified as productive. Furthermore, we investigated median cough epoch length and median number of cough events in a cough epoch.…”
Section: Methodsmentioning
confidence: 99%
“…A previous investigation by Smith et al has shown the ability of health care professionals to distinguish between these types of cough with a high accuracy by listening solely to the sound of cough. 17 If an epoch contained at least one productive cough event, the epoch was classified as productive. Furthermore, we investigated median cough epoch length and median number of cough events in a cough epoch.…”
Section: Methodsmentioning
confidence: 99%
“…There are three phases in a typical cough event [10] [23]. These phases are typically called the (1) initial cough sound, (2) intermediate phase, and (3) second cough sound [23]. Figure 1 presents an example COVID cough event with each phase identified.…”
Section: Cough Phase Annotationmentioning
confidence: 99%
“…For example, Chatrzarrin et al used the power variations between the first and second phase as a feature for differentiating between wet and dry cough events. Furthermore, some cough events do not contain the third phase ( Figure 2) [23]. The reduction or complete absence of this phase may also be a potential tool for differentiation.…”
Section: Cough Phase Annotationmentioning
confidence: 99%
“…A range of healthcare professionals listening to cough sounds from patients with different diseases can accurately recognize the presence–absence of airway sputum, but are poor at specifying the patient’s disease (Smith et al 2006a). The development of an automated system for ambulatory cough counting, over at least 24 hours, would revolutionize the study of cough and its importance in respiratory disease in general, and COPD in particular.…”
Section: Clinical Studies Of Cough In Copdmentioning
confidence: 99%